HARMONIZING RELIGIOUS AND INDIGENOUS VALUES AMONG THE BANUA COMMUNITY IN BERAU - R, Emelia Nurwati; Khosiin, Khamam; Khairiyah, Khairiyah (Journal of Noesantara Islamic Studies, 2026)
This study examines the harmonization of religious and indigenous values within the Banua community in Berau Regency, East Kalimantan. The research aims to explore how Islamic teachings are interpreted, practiced, and transmitted through adat (customary traditions) in everyday social life. Employing a qualitative approach grounded in interpretative phenomenological and hermeneutic perspectives, data were collected through in-depth interviews, participant observation, and document analysis involving customary leaders, religious figures, ritual practitioners, and community members. The findings reveal that religious values and adat function as complementary systems rather than competing frameworks. Islamic moral principles are embedded within customary norms, rituals, and communal practices, enabling religion to remain culturally resonant and socially meaningful. Cultural rituals such as Puncak Rasul and Terbangan (Hadrah) play a crucial role as media for value integration and intergenerational transmission. The novelty of this study lies in its empirical demonstration of harmonization as a lived, dialogical process within an underrepresented indigenous community in Kalimantan. The study implies that culturally grounded religious practices can strengthen social cohesion, cultural resilience, and moral continuity in plural societies.